The quality of public finances: bibliometric and textual analysis of publications of the Web of Science database (Research, Society and Development, 2020)
This article aimed to map scientific production on the topic of finance and from there, carry out a textual analysis on the quality of public finances. For this purpose, bibliographic research, bibliometric analysis and textual analysis were executed in publications of the Web of Science database, in the period from 1980 to 2020. This study is important once public finance is responsible for control of a country's income and expenses, in order to seeking financial balance and possibility of economic growth. The article was structured as follows: public finance concept, the quality of public finances, methods and analyzes used in research, data analysis, final considerations and references. From the results of the research, an increase in publications in years and consequently a greater number of citations on the topic could be identified. Regarding the way of disseminating academic material, the use of scientific articles stands out, Economics is the main area of study on the subject. Furthermore, in the textual analysis could be perceived that, among the three most cited articles that dealt with the quality of public finances two were published in magazines with Qualis A1 and an article in magazine B1, among the main contributions highlighted on the quality of public finances are: sustainability of finances, indicators, the impact on public finances resulting from the population increase arising from the immigration, the need for fiscal rules and government efficiency.